DAMPAK NEGATIF JUAL BELI BARANG DI ATAS PENAWARAN ORANG LAIN - Hendrianto, Hendrianto; Ridwan, A Hasan (I-Economics, 2021)
The researcher conducted this research with the intention of explaining the prohibition of selling/buying on people who are in the process of bidding on goods, both in terms of fraternity and the negative impact (consequences) that arise when bidding occurs while other people are still khiyar. This research was conducted by means of a literature review (Library Research) which uses data collection techniques in the form of documentation. For data analysis, namely literature analysis. The results show that Islam recommends maintaining brotherhood, especially in bargaining for goods when buying and selling so as not to result in market distortion, loss of willingness, violating the value of tolerance, unfair competition, the emergence of hatred, conflict of needs, and a weak level of prudence.